The virulence markers of Salmonella enterica serovar Typhimurium. Different phage-type strains isolated in Slovakia - Majtán, V; Majtánová, L; Szabóová, M (Folia microbiologica, 2005)
Phage-typing determination of cell-surface hydrophobicity, motility, and serovar-specific virulence plasmid was performed in a collection of 154 clinical isolates of S. enterica serovar Typhimurium (SeT) isolated in Slovakia. All isolates were also examined in PCR for the presence of both stn (enterotoxin) and iroB (siderophore) genes. The DT104 was the definitive phage type most frequently identified (37.7 %), the second most frequently isolated phage type was DT41 (5.8 %); the occurrence of other phage types was not epidemiologically significant. On the basis of virulence-marker investigation, 46.1 % of isolates were hydrophobic in the assay of bacterial adherence to xylene, and 97.4 % were hydrophobic in salt-aggregation test. Motility of more than 50 mm was expressed by 20.8 % isolates. The serovar-specific 90-kb virulence plasmid was contained in 138 (89.6 %) of isolates. All SeT isolates were found (according to PCR) to carry the Salmonella-enterotoxin (stn) gene and the siderophore (iroB) gene. The increasing incidence of SeT DT104 human strains in Slovakia requires continuous attention; this can be markedly improved by surveillance efficiency and made possible by determining relationships between sporadic isolates.
Keywords: Humans; fagotypizace; Hydrophobic and Hydrophilic Interactions; Virulence; lidé; plazmidy; zvířata; Bacterial Adhesion; virulence; Slovakia; Slovenská republika; pohyb; bakteriální adheze; Salmonella typhimurium; Siderophores; polymerázová řetězová reakce; Polymerase Chain Reaction; Movement; siderofory; Animals; Bacteriophage Typing; Plasmids; Enterotoxins; enterotoxiny; hydrofobní a hydrofilní interakce